Successful presurgical management by intravenous steroid therapy in spinal dural arteriovenous fistula. Issue 3 (29th May 2013) - Matsumoto, Hideyuki; Ichi, Shunsuke; Bannai, Taro; Igeta, Yukifusa; Suzuki, Ichiro; Hashida, Hideji
Abstract The present report describes the case of a 57‐year‐old male patient with spinal dural arteriovenous fistula (AVF). During the diagnostic examination, intravenous steroid therapy was implemented. The next day, the patient's symptoms were mildly improved and magnetic resonance imaging showed that the spinal cord swelling was markedly reduced. After the angiographic diagnosis of spinal dural AVF fed from the radicular artery originating from the sixth intercostal artery, the shunts were surgically interrupted by cutting the drainage vein. Clinical deterioration after steroid therapy was reported in several previous papers on this disorder. Based on the present case, however, we propose the possibility that intravenous steroid therapy is a viable option for presurgical management.